Artificial urinary sphincter cuff size predicts outcome in male patients treated for stress incontinence: results of a large central european multicenter cohort study - Queißert, Fabian; Nyarangi-Dix, Joanne (International neurourology journal, 2019)
Purpose: The aim was to study the correlation between cuff size and outcome after implantation of an AMS 800 artificial urinary sphincter. Methods: A total of 473 male patients with an AMS 800 sphincter implanted between 2012 and 2014 were analyzed in a retrospective multicenter cohort study performed as part of the Central European Debates on Male Incontinence (DOMINO) Project. Results: Single cuffs were implanted in 54.5% and double cuffs in 45.5% of the patients. The cuffs used had a median circumference of 4.5 cm. Within a median follow of 18 months, urethral erosion occurred in 12.8% of the cases and was associated significantly more often with small cuff sizes (P<0.001). Multivariate analysis showed that, apart from cuff size (P=0.03), prior irradiation (P<0.001) and the penoscrotal approach (P=0.036) were associated with an increased erosion rate. Continence rate tended to be highest with median cuff sizes (4–5.5 cm). Conclusions: Apart from irradiation and the penoscrotal approach, small cuff size is a risk factor for urethral erosion. Results are best with cuff sizes of 4.5–5.5 cm.